Mitral regurgitation increases systolic strains in remote zone and worsens left ventricular dyssynchrony in a swine model of ischemic cardiomyopathy - Kikuchi, Yuta; Onohara, Daisuke; Silverman, Michael; King, Chase L.; Tom, Stephanie K.; Govin, Riya; Guyton, Robert A.; Padala, Muralidhar (Frontiers in Cardiovascular Medicine, 2024)
Background Ischemic mitral regurgitation (IMR) imposes volume overload on the left ventricle (LV), accelerating adverse LV remodeling. In this study, we sought to investigate the impact of volume overload due to IMR on regional myocardial contractile mechanics. Methods Ten Yorkshire swine were induced with myocardial infarction (MI) by occluding the left circumflex coronary artery (LCx). Cardiac MRI was performed at baseline (BL) and 2.5 months (2.5M) post-MI. IMR was quantified with epicardial echocardiography 3 months post-MI. The animals were then assigned to 2 groups: no/mild MR (nmMR, n = 4) and moderate/severe MR (msMR, n = 6). MRI images were analyzed to assess infarction size, end-diastolic and end-systolic volume (EDV and ESV, respectively), ejection fraction (EF), longitudinal strain (LS), circumferential strain (CS), and systolic dyssynchrony index (SDI). The myocardial region was divided into infarction, border, and remote zones based on the LCx-supplied region. Results There was no difference in the infarction size. Group-wise comparison of LS and CS between BL and 2.5M demonstrated that LS and CS in the infarction zone and the border zone decreased at 2.5M in both groups. However, LS and CS in the remote zone were elevated only in the msMR group (LS: −9.81 ± 3.96 vs. −12.58 ± 5.07, p < 0.01; CS; −12.78 ± 3.81 vs. −16.09 ± 3.33, p < 0.01) at 2.5M compared to BL. The SDI of CS was significantly elevated in the msMR group (0.1255 vs. 0.0974, p = 0.015) at 2.5M compared to BL. Conclusions Elevated LS and CS in the remote zone were observed in moderate/severe MR and ventricular dyssynchrony. These elevated cardiac strains, coupled with ventricular dyssynchrony, may contribute to the progression of MR, thereby accelerating heart failure.